WeChat news contact among Chinese youth and impact on political participation: the role of social capital, political trust, and media literacy - Tang, Qingqing; Kamarudin, Syafila; Zhang, Xin (RedFame Publishing, 2024)
Several recent studies have found that social media positively influences the online political participation behavior of youth. However, only a few studies have explored the political participation behavior of Chinese youth on specific social media, such as WeChat, the most widely used mobile social media in China. To bridge this gap, this study examines Chinese youths’ contact with WeChat and its subsequent impact on political participation. The study uses a questionnaire to collect data and uses the SPSS 25.0 version to analyse data. The findings show that: (1) Chinese youths' WeChat news contact positively affects their WeChat political participation; (2) Chinese youths' social capital positively affects their political trust; (3) social capital and political trust play a partially mediating role between youths' WeChat news contact and youths' WeChat political participation; (4) media literacy plays a moderating role between youth WeChat news contact and youth WeChat political participation. Implications and limitations of the ﬁndings are discussed.